2011
DOI: 10.1016/j.ejcts.2010.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of stage III thymic tumors: a multi-institutional review from four Italian centers☆

Abstract: Multimodality treatment of stage III thymic tumors achieved good survival. Radical surgery, even at recurrence, seems to be the most important prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 24 publications
2
24
1
1
Order By: Relevance
“…There may be statistical significance accompanied by the increase of samples. Our data is consistent with the outcomes of previous studies that reoperation might result in better survival than non-surgery treatment, especially when complete resection was possible [3,4,[6][7][8]10,12,[16][17][18][19][20][21]. A meta- advanced stage (III/IV) thymoma or incomplete resection [4,8,[28][29][30][31][32], theoretically, adjuvant treatment may also improve the outcomes of recurrent thymoma.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…There may be statistical significance accompanied by the increase of samples. Our data is consistent with the outcomes of previous studies that reoperation might result in better survival than non-surgery treatment, especially when complete resection was possible [3,4,[6][7][8]10,12,[16][17][18][19][20][21]. A meta- advanced stage (III/IV) thymoma or incomplete resection [4,8,[28][29][30][31][32], theoretically, adjuvant treatment may also improve the outcomes of recurrent thymoma.…”
Section: Discussionsupporting
confidence: 81%
“…Whereas, unlike the previous studies [3,4,[6][7][8]12,[16][17][18][19][20][21], we observed that much high percent (71.4%) of patients who underwent reoperation received adjuvant chemotherapy, radiotherapy, or chemoradiotherapy, which may improve the treatment outcomes of recurrent thymoma and confound the benefit of reoperation. Based on that adjuvant treatment can improve the outcomes of patients who have median survival interval after recurrence of the chemotherapy group was higher compared with the group of patients without retreatment, but no statistical significance (P=0.062).…”
Section: The Outcomes Of Recurrent Thymomacontrasting
confidence: 53%
“…Of these great vessels, the SVC is the most commonly affected (57,58), with varying extent of involvement, ranging from partial compression or invasion, to the development of a SVC syndrome (59). The exact incidence of SVC involvement in mediastinal tumors is unknown, due to the relative rareness of this pathology.…”
Section: Involvement Of the Svcmentioning
confidence: 99%
“…Also, the overall survival (OS) and the cancer free survival (CFS) decrease in advanced stage TETs, especially after incomplete resections, while the recurrence rate increases in stage III-IV TETs and in more aggressive histological tumor subtypes (1,(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Furthermore, more than 50% of these patients may develop tumor recurrences after surgery and postoperative RT (12)(13)(14) being pleura, pericardium, diaphragm and lung the most common sites of tumor relapses. Also, the overall survival (OS) and the cancer free survival (CFS) decrease in advanced stage TETs, especially after incomplete resections, while the recurrence rate increases in stage III-IV TETs and in more aggressive histological tumor subtypes (1,(11)(12)(13)(14).…”
mentioning
confidence: 99%